2021
DOI: 10.17816/nb77773
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characteristics of the alpha-rhythm of the electroencephalogram in depressive disorders

Abstract: The aim of research was to study the quantitative characteristics of the alpha rhythm in patients with depressive disorders. Material and methods. The study sample consisted of patients who were treated at the clinic of the Research Institute of Mental Health (department of affective states) Tomsk NIMC. A total of 84 patients (67 women, 17 men) aged 20 to 60 years with mood disorders in the framework of a depressive episode, recurrent depressive disorder and dysthymia were examined. An electroencephalogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Considerable data now exists on the changes that take place in the alpha power in depressive disorders of various origins [10-17] . However, only a few studies into the activation reaction in patients with depressive disorders can be found in the literature [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Considerable data now exists on the changes that take place in the alpha power in depressive disorders of various origins [10-17] . However, only a few studies into the activation reaction in patients with depressive disorders can be found in the literature [20] .…”
Section: Introductionmentioning
confidence: 99%